O tempo jurídico e a homologação tácita - Zomer, Sílvia Regina (2016)
This doctoral thesis aims to analyze time as an instituting element of the juridical reality, specifically, in the conformation of the tacit homologation. We delimit the context that circumscribes the field of investigation of this work to the positive law, considering it, a priori, as a communicational phenomenon capable of regulating intersubjective behaviors from the set of valid legal norms, conveyed by prescriptive statements produced under certain conditions of space and time, which is why we seek to base the presuppositions systematized by the Philosophy of Language and in Logical-Semantic Constructivism, conceived as an appropriate approximation method to conduct the analysis of the prescriptive language of law, in its syntactic, semantic and pragmatic aspects, attempting to demonstrate, conclusively, that the tacit approval is only lapse juridical fact, instituted according to art. 150, § 4 of the National Tax Code